Photoplethysmography telemonitoring during the first week after atrial fibrillation ablation: Feasibility and clinical implications. (19th May 2022) - Manninger, M; Rohrer, U; Eberl, AS; Andrecs, L; Loibnegger, S; Pratl, B; Hermans, A; Hendriks, J; Pluymaekers, NAHA; Zirlik, A; Linz, D; Scherr, D
Abstract: Funding Acknowledgements: Type of funding sources: None. The incidence of early atrial fibrillation (AF) recurrence within the first week after AF ablation and its predictive value for late AF recurrences are unclear. TeleCheck-AF is a remote on-demand mobile health (mHealth) infrastructure, which is based on a mobile phone app using photoplethysmography (PPG) technology (Fibricheck) allowing rate and rhythm monitoring through teleconsultations. The feasibility and clinical implications of PPG telemonitoring specifically during the first week after atrial fibrillation ablation is unknown. Methods: Within the TeleCheck-AF project, the Medical University offered a total of 382 consecutive patients undergoing AF ablation (between June 1st 2020 and December 15th 2021) photoplethysmography (PPG) telemonitoring with "FibriCheck" during the first week after the ablation procedure. Patients received a QR code for activation of the software on their smartphone and were connected to the clinician's telemedicine portal. They were instructed to perform rhythm monitoring three times per day and in case of symptoms. Clinicians assessed the tracings and contacted the patients if therapeutic steps were indicated. Results: In total, 119 patients (31%) agreed to perform telemonitoring after ablation. Patients undergoing telemonitoring were younger compared to those who refused participation (58±10years vs. 62±10years, p<0.001). 34% were female, median CHA2DS2-VASc-Score was 1 (0-6). 62% of patients had paroxysmal AF and 37% had persistent AF. One of four patients (24%) had already undergone previous ablations. Most index ablations were radiofrequency ablations (89%; 7% cryo; 4% pulsed field ablation). Median follow up duration was 281 (16-620) days. 27% of patients had tracings suggestive of AF in the week following the index ablation. Telemonitoring resulted in clinical interventions ins 24% of patients: amiodarone was started in 8%, class I antiarrhythmic drugs were up titrated in 7%, cardioversion was scheduled in 5%, antiarrhythmic drugs were reduced due to symptomatic bradycardia in 3% of patients. During follow-up, 22% of patients had ECG-documented AF recurrences. PPG recordings suggestive of AF in the week after ablation were predictive of late recurrences (p<0.001). Conclusion: Rhythm monitoring with a PPG-based mHealth application was feasible and often resulted in clinical interventions. Due to its high availability, PPG-based follow-up actively involving patients after AF ablation may close a diagnostic and prognostic gap and increase active patient-involvement. Figure 1: Schematic overview of the telemonitoring process. After the ablation, the patient measures PPGs for one week, dashboard view for clinician shows regular rhythm (green, atrial fibrillation (red) and unclear tracings (blue).